Loud & clear : 5 steps to say what you mean and get what you want - Berg, Karen (Karen E.) (Career Press, 2008)
'Loud & Clear' is for everyone who needs to know how to get what she or she wants from anyone. Whether you need to get a message through to an employer, team, committee, your staff, your neighbour, teacher, student or spouse, this book will show you how to get their attention.